Hemodynamic Effect of Different Kinds of Venous Augmentation in a Pig Transmidline Flap Model of DIEP Flap - Minqiang, Xin; Jie, Luan; Dali, Mu; Lanhua, Mu (Journal of Reconstructive Microsurgery, 2013)
Background Venous augmentation enhances the viability of the deep inferior epigastric perforator (DIEP) flap. We compared the efficacy of three venous superdrainage procedures on survival area and hemodynamics of the DIEP flap model.Methods In 24 castrated Yorkshire pigs, a true abdominal perforator-based flap was created based on four perforators arising from the deep superior epigastric vessels. Three remaining venous tracts were alternated to represent different venous augmentations of the DIEP flap. Analyzed were flap perfusion, venous blood pressure, and venous blood gas. In control animals, all three supplemental veins were ligated; the ipsilateral superficial superior epigastric vein (SSEV) was retained in the IS (ipsilateral SSZV augmented) group, the contralateral SSEV in the CS (contralateral SSZV augmented) group and the contralateral deep superior epigastric vein (DSEV) in the CD (contralateral DSZV augmented) group. The flap was then returned to its bed, and animals sacrificed on the seventh day postoperatively. DIEP flap survival was then recorded.Results All four intraoperative parameters showed improved perfusion of the distal flap area under distal venous augmentation. Efficacy was CDSEV > CSSEV > ISSEV > none. Skin islands of the CD and CS groups survived completely. In the IS and control groups, 96.33 ± 3.16% and 84.00 ± 7.55% of skin islands survived, respectively. Test groups were statistically significantly different from the control group but not from each other.Conclusions Venous superdrainage effectively enhances DIEP flap survival. Benefit was relatively the same for all procedures. An additional venous route should be preserved with large or multiterritory flaps to improve venous congestion.
Keywords: breast reconstruction; hemodynamic research; superdrain; venous augmentation